Too hot to handle, the adverse effect of heat stress on crop yield. Issue 4 (29th July 2020) - van Es, Sam W.
Abstract : A major part of the human diet is made up by seeds such as wheat, rice and maize; both as staple crops and as raw material for livestock feed. The yield of these crops is highly dependent on successful flower development, pollination and proper timing of seed set. However, significant yield loss is caused by stress factors such as excessive heat and drought, which are being exacerbated by ongoing climate change (Zhao et al. 2017). Pollen development, in particular, is highly sensitive to heat stress (Mesihovic et al. 2016) and in an effort to enhance our understanding of plant responses to heat stress, with the view of aiding breeding efforts, Bheemanahalli et al. (2020) used metabolic and hormonal profiling to investigate the regulation of heat stress tolerance in two wheat genotypes.